PERAN LAYANAN BIMBINGAN KELOMPOK UNTUK MENGATASI HAMBATAN KONSENTRASI BELAJAR ANAK SEKOLAH DASAR : kajian teori - Rina Efriyani; Leni Murni Hayati (Jurnal Pendidikan Widyaswara Indonesia, 2025)
The ability to concentrate during learning plays a crucial role in supporting the success of the educational process at the elementary school level. Learning concentration is defined as a student’s ability to focus attention on learning materials continuously for a certain period. However, in practice, many elementary school students experience concentration difficulties, as indicated by their inability to stay focused, frequent distractions from the surrounding environment, and low learning motivation. These concentration barriers not only affect academic achievement but also influence the students' social and emotional development at school. To address this problem, group counseling services emerge as a preventive and developmental guidance strategy. Group counseling is conducted in small group settings that allow students to explore problems together, share experiences, and receive emotional support from peers and counselors. Through guided discussions, relaxation techniques, social simulations, educational games, and self-reflection, students are assisted in identifying the causes of their concentration problems and finding appropriate solutions. Various literature studies show that the consistent and systematic implementation of group counseling has a significant impact on improving students’ concentration abilities. In addition, this service can increase intrinsic motivation, reduce learning anxiety, and foster more disciplined study habits. Therefore, integrating group counseling services into guidance and counseling programs at elementary schools is highly recommended as an effective effort to overcome learning concentration barriers among students.